"Digital diplomacy" and the securing of nationals in a citizen-centric world. Issue 3 (26th May 2016) - Melissen, Jan; Caesar-Gordon, Matthew
Abstract : This article examines the ways in which ministries of foreign affairs (MFAs) assisting nationals abroad are adapting to the demands of the digital age, how their established work processes are being questioned, and what is the significance of newly emerging communication patterns in the context of one of the principal MFA functions. Policy innovation in this sector helps diplomats understand the importance of adopting communicative styles that are in sync with wider societal trends. We review lessons that MFAs have learned and are still learning from operating in data-rich and real-time environments during international crises, and restrictions on their ability to innovate. A more networked "duty of care", drawing on the use of social media and more analytical digital collaboration with the non-governmental sector, is producing results and often making collaboration a condition of success. Informational aspects of securing nationals abroad are increasingly citizen-driven. We argue that the "digital shift" in consular assistance reveals how MFA effectiveness and legitimacy are becoming more dependent on citizen participation, and that achieving policy objectives has become more underpinned by understanding trends in people's online behaviour. In the years ahead, MFAs are likely to become more explicit in making the argument that a digitally literate and a natively digital citizenry is expected to help governments assisting nationals abroad, and reinforce their emerging view that nationals abroad should assume more responsibility for their own security.